2020
DOI: 10.7717/peerj.8406
|View full text |Cite
|
Sign up to set email alerts
|

New protocol for successful isolation and amplification of DNA from exiguous fractions of specimens: a tool to overcome the basic obstacle in molecular analyses of myxomycetes

Abstract: Herbarium collections provide an essential basis for a wide array of biological research and, with development of DNA-based methods, they have become an invaluable material for genetic analyses. Yet, the use of such material is hindered by technical limitations related to DNA degradation and to quantity of biological material. The latter is inherent for some biological groups, as best exemplified by myxomycetes which form minute sporophores. It is estimated that ca. two-thirds of myxomycete taxa are represente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…For some collections, the protocol based on direct polymerase chain reaction (PCR) method, as described by Janik et al (2020), was applied; for others, total DNA was extracted from 4-6 adjacent sporocarps from each sample as described in Fiore-Donno et al (2012). Samples in safelock Eppendorf tubes containing one 3-mm tungsten carbide bead were frozen at −40 C and then subjected to mechanical disruption in a TissueLyser II bead mill (Qiagen, Hilden, Germany).…”
Section: Dnamentioning
confidence: 99%
See 1 more Smart Citation
“…For some collections, the protocol based on direct polymerase chain reaction (PCR) method, as described by Janik et al (2020), was applied; for others, total DNA was extracted from 4-6 adjacent sporocarps from each sample as described in Fiore-Donno et al (2012). Samples in safelock Eppendorf tubes containing one 3-mm tungsten carbide bead were frozen at −40 C and then subjected to mechanical disruption in a TissueLyser II bead mill (Qiagen, Hilden, Germany).…”
Section: Dnamentioning
confidence: 99%
“…Primer KEF_R3 published in Wrigley de Basanta et al (2017) was employed as a reverse primer. PCR conditions were those described in Wrigley de Basanta et al (2015) and Janik et al (2020). Additionally, if amplification failed, a seminested PCR was conducted using newly designed SF02 (TCATATGCTTGTCCCGAAG) and EF04 (TGGGTGT TGGACAAACTC) as forward primers for 18S and EF-1α, respectively, in a total volume of 20 µl containing: 1× AccuTaq LA Buffer (Sigma-Aldrich, St. Louis, Missouri), 0.5 mM of each dNTPs, 0.4 µM of each primer, 0.1% bovine serum albumin, 0.05 U REDAccuTaq LA DNA Polymerase (Sigma-Aldrich), and 1 µL of purified product from the first PCR adjusted with double-distilled water (ddH 2 O), with the following cycling conditions: initial denaturation for 30 s at 96 C, followed by 35 cycles of 1 min at 94 C, 45 s at 52 C, and 10 min at 68 C, and final elongation for 30 min at 72 C. Forward and reverse directions of each region were amplified and analyzed with an ABI 3730XL automated sequencer (Macrogen, Seoul, South Korea) or with an ABI 3500 sequencer (Applied Biosystems, Foster City, California) at the W. Szafer Institute of Botany, Polish Academy of Sciences.…”
Section: Dnamentioning
confidence: 99%
“…We did not encounter any cross-contamination between the two groups. As explained in Novozhilov et al (2013) and Janik et al (2020), cross-contamination between samples can be a serious problem. From this reason, the latter authors use disposable sterile syringe needles.…”
Section: Discussionmentioning
confidence: 99%
“…The technique used for sampling this group, the moist chamber, usually results in few sporangia to allow efficient DNA extraction for molecular studies, like sequencing. However, a newly protocol, proposed by Janik et al (2020), which combine micro-disruption of spores with direct PCR, by using small portions of spores from a single sporangium, should be an excellent alternative for molecular analysis of fimicolous myxomycetes, since the authors observed 94.7% effectiveness in amplifying both the dark and the brightspored myxomycetes analyzed. This direct PCR method is applied to amplify a partial nuclear small-subunit rRNA gene (18S or SSU), the most used barcode region to identify myxomycetes and to perform phylogenetic relationship analysis in the myxomycetes.…”
Section: T Papillatamentioning
confidence: 99%
“…ncbi.nlm.nih.gov/genbank/), has increased in recent years, there is still a shortage of sequences of fimicolous species. Walker et al (2017) describe the main techniques used for the ecological and biological study that, added to the new approach proposed by Janik et al (2020), should contribute to improving the knowledge of the species of fimicolous myxomycetes. Among these technologies, the terminal restriction fragment length polymorphism (TRFLP) with myxomycete SSU, denaturing gradient gel electrophoresis (DGGE) and highthroughput sequencing (e.g.…”
Section: T Papillatamentioning
confidence: 99%